2023
DOI: 10.1007/s12035-023-03381-0
|View full text |Cite
|
Sign up to set email alerts
|

Occludin Regulates HIV-1 Infection by Modulation of the Interferon Stimulated OAS Gene Family

Abstract: HIV-1-associated blood brain barrier (BBB) alterations and neurocognitive disorders are frequent clinical manifestations in HIV-1 infected patients. The BBB is formed by cells of the neurovascular unit (NVU) and sealed together by tight junction proteins, such as occludin (ocln). Pericytes are a key cell type of NVU that can harbor HIV-1 infection via a mechanism that is regulated, at least in part, by ocln. After viral infection, the immune system starts the production of interferons, which induce the express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 124 publications
(153 reference statements)
1
5
0
Order By: Relevance
“…Reports from our laboratory 25 , 31 , 33 , 35 , 36 , including data presented in Fig 2I , have shown that ocln can regulate the extent of HIV-1 infection in various cell types, including brain pericytes. However, no studies have been performed in vivo demonstrating the influence of ocln on HIV replication in the brain.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Reports from our laboratory 25 , 31 , 33 , 35 , 36 , including data presented in Fig 2I , have shown that ocln can regulate the extent of HIV-1 infection in various cell types, including brain pericytes. However, no studies have been performed in vivo demonstrating the influence of ocln on HIV replication in the brain.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, ocln can regulate HIV-1 budding from the infected cells by forming a complex with caveolin-1 and ALIX 35 . While the majority of research on the regulatory role of ocln on HIV-1 infection was performed on brain pericytes 25 , 31 , 35 , the findings were confirmed in human primary macrophages, differentiated monocytic U937 cells, and HEK-293 cells 43 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations